تأليف الكتاب المصاحب لتنمية مهارة الكلام ( بحث تجريبـي في المدرسة المتوسطة الإسلامية الحكومية فريغين باسوروان ) - Agus Harianto (PPs UIN Maulana Malik Ibrahim Malang, 2010)
The Speaking is one of the factors from value the speaking skill. In the instructional need good design of matters to support the forming of communication environment on that the matter. During that the matter leaned normative design, stark and poor of communicative vocabulary so value in the speaking skill not reached.At MTsN Prigen have problem about the matter for instructional classroom and weakness ability of speaking skill from students. 1). Not optimally in using the matter book. Since KTSP act, apparently still using matter of book instructional with KBK 2004, so expired to use in KTSP season. The topics there is small variation for it the user must choose the agreeable topics. 2).The speaking skill of students so weak and late, result from the content of speaking matter that not communication design. 3).The instructional needs a book with design of development speaking skill for anticipation of ability late from students with their skill. So that, prepare of vocabularies and sentences have a basis communication necessary every day.The goal of the experiment is: 1).The need a student book for material text like a glossary with dictionary speaking design specially for speaking skill development. 2).To exam the book using in act classroom activities. The hoping is the book can indicate that there is escalation student speaking skill. As for the main results of this research are: (1). produced the book that the content needed in activities of student communication. (2). Motivation of student is build with the book in class teaching with agreeable strategic and interesting value in the application. (3). communication design of this student's book can help speaking ability faster than conventional book in speaking skill design.Design of development content and explanation technique from this book must be continue to do for this book in order to get a book with curriculum content congruently to help in studying and practice for student speaking skill development next time.Keywords: Text book, Development, Speaking Skill